The borders of violence: temporary migration and domestic and family violence - Segrave, Marie Therese (Routledge studies in criminal justice, borders and citizenship, 2025)
"This book explores the structural harm of borders and non-citizenship, specifically temporary non-citizenship, in the perpetuation of domestic and family violence (DFV)"--